Review of mechanical vapour compression refrigeration system part 2: performance challenge - Mahmood, Raid; Ali, Omar; Al-Janabi, Abdullah; Al-Doori, G.; Noor, M.M. (Zielona Góra: Uniwersytet Zielonogórski)
Reducing energy consumption and providing high performance for a vapour compression refrigeration system are big challenges that need more attention and investigation. This paper provides an extensive review of experimental and theoretical studies to present the vapour compression refrigeration system and its modifications that can be used to improve system`s performance and reduce its energy consumption.
Keywords: vapour compression; refrigeration systems; cycle; coefficient of performance (COP)